The Representation of Gender Inequality in the Novel Gadis Pantai and Its Relevance to Educational Practice - Erliesty Devi Pramesthi; Prissilia Prahesta Waningyun (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study analyzes the representation of gender injustice and the construction of the main character’s image in Pramoedya Ananta Toer’s Gadis Pantai through a feminist literary criticism approach and explores its relevance as a learning source in literary education. Using a descriptive qualitative method, the research examines narrative excerpts that reflect forms of gender oppression, including marginalization, subordination, stereotyping, psychological and sexual violence, objectification, and the denial of educational rights. Data were collected through document analysis, content review, and coding procedures, followed by content analysis to interpret the meanings embedded in the text. The findings indicate that the main character is positioned as a subordinated and silenced subject shaped by patriarchal norms and class hierarchy, while her physical, psychological, and social portrayals reveal the deep-rooted mechanisms of structural gender inequality. These findings have pedagogical significance: the novel can be used as a literary learning material to guide students in understanding gender awareness, empathy, and critical thinking about social injustice. By integrating feminist perspectives into literary learning, educators can encourage students to recognize discrimination portrayed in literature and relate it to real-world contexts, thereby strengthening character education and gender equality values.